2007
DOI: 10.1086/511052
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scan for Tourette Disorder in Affected-Sibling-Pair and Multigenerational Families

Abstract: Tourette disorder (TD) is a neuropsychiatric disorder with a complex mode of inheritance and is characterized by multiple waxing and waning motor and phonic tics. This article reports the results of the largest genetic linkage study yet undertaken for TD. The sample analyzed includes 238 nuclear families yielding 304 "independent" sibling pairs and 18 separate multigenerational families, for a total of 2,040 individuals. A whole-genome screen with the use of 390 microsatellite markers was completed. Analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…The present study employed the diagnostic assessment procedure recommended by the Tourette Syndrome Association International Consortium for Genetics (Tourette Syndrome Association International Consortium for Genetics (TSAICG), 2007). The Structured Clinical Interview for DSM-IV-TR Axis I Disorders, research version, patient edition , a semistructured clinician administered interview (SCID; First, Spitzer, Gibbon, & Williams, 2002) was administered in order to establish and screen for DSM-IV diagnoses.…”
Section: Methodsmentioning
confidence: 99%
“…The present study employed the diagnostic assessment procedure recommended by the Tourette Syndrome Association International Consortium for Genetics (Tourette Syndrome Association International Consortium for Genetics (TSAICG), 2007). The Structured Clinical Interview for DSM-IV-TR Axis I Disorders, research version, patient edition , a semistructured clinician administered interview (SCID; First, Spitzer, Gibbon, & Williams, 2002) was administered in order to establish and screen for DSM-IV diagnoses.…”
Section: Methodsmentioning
confidence: 99%
“…There is widespread agreement that genetics plays a significant role in TD etiology based on twin and family studies (Browne et al, 2015; Mataix-Cols et al, 2015; Pauls et al, 1981, 1991; Price et al, 1985). To date, non-parametric linkage analyses (The Tourette Syndrome Association International Consortium for Genetics, 1999, 2007) and a genome-wide association study (Scharf et al, 2013) have not yet led to reproducible, statistically significant findings. Studies of rare pedigrees have identified putative risk genes expressed in the developing striatum and mediating neurite outgrowth (Abelson et al, 2005; Stillman et al, 2009) or involved in histaminergic neurotransmission (Ercan-Sencicek et al, 2010), signal transduction and cell adhesion (Lawson-Yuen et al, 2008; Verkerk et al, 2003), or serotonin transport (Moya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a sibling who also carried the NLGN4X deletion had a diagnosis of TD and ADHD, and the carrier mother was described as having a learning disorder, anxiety, and depression. Of note, the region identified on chromosome 2p 24 that was inserted into 7q35-q36 lies under the genome-wide significant linkage peak reported by the TSAICG 1516 .…”
Section: Resultsmentioning
confidence: 90%
“…However, when the study was extended to 238 sib pairs and 18 large multigenerational families, the evidence for linkage in these regions on chromosomes 4 and 8 diminished. However, a locus on chromosome 2p was detected that achieved genome-wide significance (p=9.8×10 −8 ) 1516 . Several other linkage studies have resulted in logarithm of the odds (LOD) scores approaching genome-wide significance 1720 , but only one to date 21 has led to the identification of a mutation that alters the structure or function of a transcript mapping within or near a suggestive linkage region.…”
Section: Resultsmentioning
confidence: 99%